Janus kinase 1 inhibitor abrocitinib for isolated nail lichen planus: a case report and literature review - Juan He; Yi Yang (Taylor & Francis Group, 2024)
Aim This study aims to evaluate the efficacy and safety of the Janus kinase 1 (JAK1) inhibitor abrocitinib for treating nail lichen planus (NLP) and to review available case reports documented in English.Methods We reported the first case of a patient with isolated NLP treated with the selective JAK1 inhibitor abrocitinib. The patient received 100 mg of oral abrocitinib daily.Results After 6 months, the patients showed 82.35% improvements in the Dermatology Life Quality Index (DLQI) and 79.17% improvement in the Nail lichen planus severity index (tNLPSI), which were consistent with the clinical improvement, correlating with clinical improvement. In the subsequent 6 months, the dose was reduced to 100 mg every other day, with further improvement in onycholysis.Conclusions This case suggests that abrocitinib can be both safe and effective for treating NLP.